Article Commentary: Nonclassical Symptoms of Primary Hyperparathyroidism and Their Response to Parathyroidectomy. Issue 4 (April 2013) - Alex, Gillian; Morris, Lilah; Pasieka, Janice; Perrier, Nancy
An estimated 100, 000 new patients are diagnosed with primary hyperparathyroidism (PHPT) each year in the United States. 1 In the past, patients with PHPT typically presented with "stones, bones, abdominal groans, and psychic moans" but today patients often present with more subtle symptoms and physiologic changes associated with earlier stages of disease. Patients without the classic symptoms of PHPT are often referred to as "asymptomatic." These patients frequently pose a conundrum for clinicians. Uncertainties remain as to which symptoms truly represent PHPT and which are related to comorbidities or the aging process. To address these uncertainties, we review most recent literature regarding the nonclassical manifestations of PHPT and their response to parathyroidectomy.